Ultrafast, highly sensitive, flexible textile-based humidity sensors made of nanocomposite filaments. (June 2022) - He, Z.; Zhou, G.; Oh, Y.; Jung, B.-M.; Um, M.-K.; Lee, S.-K.; Song, J.Il; Byun, J.-H.; Chou, T.-W.
Abstract: Wearable electronics are promising next-generation smart textiles for human-computer interaction, health monitoring, and other applications. However, integrating electronic functions into strong, highly deformable electronic textiles and maintaining their functionalities during wear is a great challenge. Herein, we report ultrafast, highly sensitive, textile-based humidity sensors made of single-walled carbon nanotube (SWNT)/polyvinyl alcohol (PVA)/lithium chloride (LiCl) nanocomposite filaments fabricated via a wet-spinning and a solvent exchange process. The SWNT/PVA/LiCl textile-based humidity sensors exhibited excellent stabilities during deformation and high sensitivities with 6-fold resistance variations over a wide range of relative humidity (RH) conditions. The ultrafast responses of the sensors were attributed to the quick deliquescence of LiCl during contact with water molecules and the simultaneous conductivity change caused by the generated ions. The as-prepared sensors responded well to human breathing and real-time humidity changing, which could distinguish different breaths and microclimate changes. Such outstanding sensing performances of our textile-based sensors, in combination with their mechanical flexibilities, enable the facile integration of high-performance humidity sensors onto textile substrates for real-time microclimate monitoring. Graphical abstract: